Facing the unknown perpetrator – part I. An overview of the results and limits of forensic DNA phenotyping [Withdrawn by the author.] (Academic Journal of Internal Affairs, 2021)
Study withdrawn by author.
Keywords: forensic; DNA; phenotyping; genetics